Signatures of selection in Angus and Hanwoo beef cattle using imputed whole genome sequence data - Nawaz, Muhammad Yasir; Savegnago, Rodrigo Pelicioni; Lim, Dajeong; Lee, Seung Hwan; Gondro, Cedric (Frontiers in Genetics, 2024)
In this study, we detected signatures of selection in Hanwoo and Angus beef cattle using allele frequency and haplotype-based methods based on imputed whole genome sequence variants. Our dataset included 13,202 Angus animals with 10,057,633 imputed SNPs and 10,437 Hanwoo animals with 13,241,550 imputed SNPs. The dataset was subset down to 6,873,624 SNPs in common between the two populations to identify within population (runs of homozygosity, extended haplotype homozygosity) and between population signals of selection (allele fixation index, extended haplotype homozygosity). Assuming these selection signals were complementary to each other, they were combined into a decorrelated composite of multiple signals to identify regions under selection for each of the breeds. 27 genomic regions spanning 25.15 Mb and harboring 360 genes were identified in Angus on chromosomes 1,3, 4, 5, 6, 7, 8, 12, 13, 14, 16, 20, 21 and 28. Similarly, in Hanwoo, 59 genes and 17 genomic regions spanning 5.21 Mb on chromosomes 2, 4, 5, 6, 7, 8, 9, 10, 13, 17, 20 and 24 were identified. Apart from a small region on chromosome 13, there was no major overlap of selection signals between the two breeds reflecting their largely different selection histories, environmental challenges, breeding objectives and breed characteristics. Positional candidate genes identified in selected genomic regions in Angus have been previously associated with growth, immunity, reproductive development, feed efficiency and adaptation to environment while the candidate genes identified in Hanwoo included important genes regulating meat quality, fat deposition, cholesterol metabolism, lipid synthesis, neuronal development, and olfactory reception.